Common Causes of Congenital Deafness Diagnosed on Computed Tomography and Magnetic Resonance Imaging in a Tertiary Care Diagnostic Center in Southern Punjab - Aziz, Mubashrah; Latif, Atif; Sadiq, Nousheen; Aziz, Musfirah; Hakim, Abdul; Khan, Nadia (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the causes of congenital deafness in children presenting to a tertiary care diagnostic center in Southern Punjab.Study Design: Analytical cross-sectional study.Place and Duration of Study:  Department of Radiology, Combined Military Hospital, Multan, Pakistan, from Aug 2021 to Jul 2023.Methodology: A total of 56 children,